Combining theory and experiment in lithium–sulfur batteries: Current progress and future perspectives. (January 2019) - Chen, Xiang; Hou, Tingzheng; Persson, Kristin A.; Zhang, Qiang
Graphical abstract: Abstract: Lithium–sulfur (Li–S) batteries are considered as promising candidates for next-generation energy storage devices due to their ultrahigh theoretical gravimetric energy density, cost-effectiveness, and environmental friendliness. However, the application of Li–S batteries remains challenging, mainly due to a lack of understanding of the complex chemical reactions and associated equilibria occurring in a working Li–S system. In this review, the typical applications of computational chemistry in Li–S battery studies, correlating to characterization techniques, such as X-ray diffraction, infra-red & Raman spectra, X-ray absorption spectroscopy, binding energy, and nuclear magnetic resonance, are reviewed. In particular, high-accuracy calculations and large-scale models, materials genome, and machine-learning approaches are expected to further advance computational design for the development of Li–S batteries and related fields.